2010
DOI: 10.1117/12.865099
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil surface BRDF using an imaging spectrometer

Abstract: Ground reference data are important for understanding and characterizing angular effects on the images acquired by satellite sensors with off-nadir capability. However, very few studies have considered image-based soil reference data for that purpose. Compared to non-imaging instruments, imaging spectrometers can provide detailed information to investigate the influence of spatial components on the bidirectional reflectance distribution function (BRDF) of a mixed target. This research reported in this paper in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…has been observed as a bell curve with the maximum occurring where the sample is sensed at nadir. 25,27 Signal drops off fairly uniformly as the sensing zenith angle increases, because shadowing changes very little when the sensor is moved along the azimuthal axis perpendicular to the sun. This can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…has been observed as a bell curve with the maximum occurring where the sample is sensed at nadir. 25,27 Signal drops off fairly uniformly as the sensing zenith angle increases, because shadowing changes very little when the sensor is moved along the azimuthal axis perpendicular to the sun. This can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] This preferential scattering is due to an absence of particle shadowing and occlusion within the line of sight between the sensor and the sample. Unique reflectance features also arise from the intimate mixing of grains, scattering albedo, grain transmittance, and sample density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, a number of different designs have been developed for measurement of hyperspectral HCRF. These have included the Swiss Field-Goniometer System (FIGOS), 37 , 38 dual-view FIGOS, 39 the European Goniometric Facility, 38 the University of Lethbridge Goniometer System (ULGS) 40 , 41 and ULGS-II, 5 , 42 the Automated Spectro-Goniometer (ASG), 7 the Compact Laboratory Spectro-Goniometer, 43 a robotic laboratory goniometer system, 44 the Manual Transportable Instrument platform for ground-based Spectro-Directional observations, 45 the Mobile Unit for Field Spectroradiometric Measurements, 46 and systems based on unmanned aerial vehicles, 47 among others 48 50 While some systems have been designed primarily for the laboratory, 38 , 43 , 44 others are primarily field instruments 37 , 40 , 45 , 46 .…”
Section: Instrumentationmentioning
confidence: 99%
“…Second, the substrate under the canopy layer is assumed to be a Lambertian surface. Field studies have observed the effects of bidirectional reflectance distribution function (BRDF) for soils (Liang and Townshend, 1996;Wang et al, 2010), and coupled soil and vegetation models (Ni and Li, 2000;Verhoef and Bach, 2007) should be tested to understand the effects of soil BRDF on canopy photosynthesis. Third, we assume maximum constant leaf stomatal conductance over the growing season.…”
Section: Assumptions and Future Improvementsmentioning
confidence: 99%